Statistical analysis of the dissemination of cultural heritage in traditional and social media in Burundi - Nsavyimana, Remy (ESI Preprints (European Scientific Journal, ESJ), 2025)
The objective of this work is to determine the place of cultural heritage in newspapers radio and television broadcasts as well as online media. We analysed metadata from the Conseil National de la Communication (CNC) and Annuaire du Secteur de la Communication et des Médias (ASCM 2019). The choice of these traditional or online radio and television stations is the responsibility of these state structures. Thus, 13 radio stations, including 2 public radio stations and 11 private radio stations dealing with 11397 subjects in the spoken news, are the subject of research. A total of 354 radio program were analyzed. In the online media, 765 articles were posted. The results show that cultural information is relegated to second place in radio and television news and online media. Only 53 cultural items out of a total of 765, i.e. a rate of 0.6%, are relayed online. Jimbere Magazine took the lead with 39 cultural items out of a total of 53 broadcasts on the 13 radio stations, a rate of 73.5%. The political and educational sections attracted more attention from the public and private media, with 160 and 116 items respectively, a rate of 20% and 15%. Out of 11,397 items covered in the news on 13 radio stations broadcasting in Burundi, 11 items relating to cultural heritage were broadcast, accounting for 0.43%.